Mesenteric Cystic Lymphangioma in Pediatric Patient: A Rare Intra-Abdominal Tumor Management in Rural Country Case Report - Kusuma, Perdhana; Putra, Muhammad David Perdana; Suwardi, Suwardi (Open Access Macedonian Journal of Medical Sciences, 2021)
Introduction: Mesenteric Cystic Lymphangioma (MCL) is a benign malformation of the lymphatic system. MCL seldomly occurs with a very rare incidence of around 1: 250,000. This neoplasm is more common in pediatric patients. Symptoms can appear with various clinical features ranging from asymptomatic abdominal mass to acute abdomen. Case description: Here we report a patient with MCL: that presented with bilious vomiting, abdominal pain, and abdominal mass. The patient underwent explorative laparotomy, mass excision, and jejunal resection. Discussion: Although benign, MCL can cause other symptoms such as bleeding, torsion, or lymphangioma rupture. Therefore, MCL should be considered as one of the differential diagnoses in acute abdominal and abdominal mass cases in children. Conclusion: In conclusion, although sometimes asymptomatic and found incidentally, the MCL should be resected because it has the potential to grow and invade vital organs and cause life-threatening complications.